KURIKULUM CINTA DALAM PENDIDIKAN ISLAM: KONSEP, IMPLEMENTASI, DAN TANTANGANNYA DI ERA KONTEMPORER - Nurhuda; M.F Mauliddin An Nabawi; Meita Setya Arwidya; Mahfudzah; Muna Azka; Zilimin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Contemporary education faces various challenges, including character degradation, increasing intolerance, declining social awareness, and the impact of digitalization on students' behavior. These conditions require an educational paradigm that emphasizes not only academic achievement but also character formation grounded in Islamic and humanitarian values. This study aims to analyze the concept of the Love Curriculum from the perspective of Islamic education, examine its implementation, identify the challenges of its application, and formulate strategies to strengthen its implementation in the contemporary era. This study employed a qualitative approach using a library research design. Data were collected through document analysis of books, scholarly journal articles, educational policy documents, and primary Islamic sources, including the Qur'an and Hadith. The data were analyzed using content analysis and thematic analysis to develop a comprehensive conceptual synthesis. The findings indicate that the Love Curriculum represents an Islamic educational paradigm based on the value of rahmah (compassion), integrating character education into all educational components. Its implementation involves strengthening school policies, humanistic learning practices, teachers' role modeling, transformational school leadership, a religious school culture, collaboration with families, and authentic assessment. Despite challenges posed by globalization, digitalization, and human resource readiness, the Love Curriculum offers significant potential to develop students with strong character, moderation, and the ability to respond to the demands of the twenty-first century while maintaining their Islamic identity. Keywords: Love Curriculum; Islamic Education; Character Education.